Atlas of procedures in gynecologic oncology - Abu-Rustum, Nadeem R.; Levine, Douglas A.; Barakat, Richard R. (CRC Press, 2013)
Covering the developments in open and minimally invasive surgery, this edition includes new international contributors, and the contents list has been restructured by procedure to improve readability with high quality accompanying video procedures